Free to Choose? Economic Freedom, Relative Income, and Life Control Perceptions - Hans Pitlik; Martin Rode (Austrian Institute of Economic Research (WIFO), 2014)
Recent research has shown that the degree to which people feel they are in control of their lives is an important correlate of individual happiness, where those that feel more in control are also found to be systematically happier. In turn, the economic sources of perceived life control are only insignificantly established in the relevant literature. The present paper employs individual data from the most recent version of the World Value Survey, covering the period from 1981 to 2013, to establish the macro-determinants of individual life control. We find that living in a country with high overall economic freedom is a major determinant of feeling in control of one's own life. The effect is very similar for individuals in high and low income countries, while the impact of democracy is negligible in both cases. Interacting relative income with economic freedom, we find that - contrary to conventional wisdom - it is by far the lower income groups that derive the biggest gain of perceived life control from living in a country with comparatively high economic freedom.
Keywords: 330; Locus of control; Economic institutions; Well-Being; Democracy